Efektivitas Komunikasi Dalam Pembelajaran Bahasa Inggris - Mutiara Sofa (Penerbit Yayasan Daarul Huda Kruengmane, 2023)
This study describes the effective communication in learning English in schools. The communication method is used so that communication between the interlocutors (communication) is effectively established. Communication in learning consists of: (1) verbal communication, 2) nonverbal communication. Some of the communication models adapted in learning are Aristotle's communication model, David K. Berlo's communication model, Bovee and Thill's communication model, and the information theory communication model. The method in this research is to use a qualitative approach with descriptive methods. Data collection procedures with content analysis and library research. The result of this research is that the English teacher must be able to communicate well. Communication that must be mastered by an English teacher, namely: (1) verbal communication, this communication is determined by voice intonation and facial expressions and body movements (2) non-verbal communication This communication is conveyed by using gestures, movements, items, time, dress code, or something that can indicate a mood or feeling at a certain moment.